Development of a One-Step Multiplex PCR Assay for Differential Detection of Four species (Enterobacter cloacae, Enterobacter hormaechei, Enterobacter roggenkampii, and Enterobacter kobei) Belonging to Enterobacter cloacae Complex With Clinical Significance - Ji, Yang; Wang, Peihong; Xu, Tingting; Zhou, Yanzi; Chen, Rongchang; Zhu, Huaiqiu; Zhou, Kai (Frontiers in Cellular and Infection Microbiology, 2021)
Enterobacter cloacae complex (ECC) is composed of multiple species and the taxonomic status is consecutively updated. In last decades ECC is frequently associated with multidrug resistance and become an important nosocomial pathogen. Currently, rapid and accurate identiﬁcation of ECC to the species level remains a technical challenge, thus impedes our understanding of the population at the species level. Here, we aimed to develop a simple, reliable, and economical method to distinguish four epidemiologically prevalent species of ECC with clinical significance, i.e. E. cloacae, E. hormaechei, E. roggenkampii and E. kobei. A total of 977 ECC genomes were retrieved from the GenBank, and unique gene for each species was obtained by core-genome comparisons. Four pairs of species-specific primers were designed based on the unique genes. A total of 231 ECC clinical strains were typed both by hsp60 typing and by species-specific PCRs. The specificity and sensitivity of the four species-specific PCRs ranged between 96.56%-100% and between 76.47%-100%, respectively. The PCR for E. cloacae showed the highest specificity and sensitivity. A one-step multiplex PCR was subsequently established by combining the species-specific primers. Additional 53 hsp60-typed ECC and 20 non-ECC isolates belonging to six species obtained from samples of patients, sewage water and feces of feeding animals were tested by the multiplex PCR. The identification results of both techniques were concordant. The multiplex PCR established in this study provides an accurate, expeditious, and cost-effective way for routine diagnosis and molecular surveillance of ECC strains at species level.